The Position and the Development Trends Private Property and Common Property - Duc, Nguyen Quang (VNU Journal of Science: Legal Studies; Vol 35 No 3DO - 10.25073/2588-1167/vnuls.4208, 2019)
The issue of the relationship between private property and common property has engaged both legal and economic scholars in a long series of controversies over the meaning, the sequence of development, and the superiority of private vs. common property. The issues debated relate to the efficiency, equity and sustainability of private property as contrasted to common property. Many scholars think of contemporary examples of common property as remnants of the past, likely to disappear during the twenty-first century. Recent research, however, has challenged the presumption that private property is necessarily superior to common property.